Common features and differences of the hypothalamic–pituitary–gonadal axis in male and female. (January 2015) - Dagklis, Themistoklis; Ravanos, Kostas; Makedou, Kali; Kourtis, Anargyros; Rousso, David
Abstract Male and female reproductive axis, comprised of hypothalamus, pituitary and gonads, present common features and differences, discussed in this review. These include the way hypothalamus regulates pituitary function, and the way pituitary, in turn, affects gonadal function. Finally, age plays an important role in axis regulation, in both genders.